Fakes and Forgers of Classical Literature : Ergo decipiatur! - Martínez García, Francisco Javier, 1965- (Metaforms, 2014)
Right from the beginning, classical literature has been embroiled with questions of authenticity, fakes, frauds, and, of course, scandal. Issues of dubious authorship, and contested authority confront philologists, critics and publishers today as surely as they did in the classical era itself. The new era of postmodernism, however, encourages us to look at the work of the forger with fresh eyes, and recent scholarship reflects this in an interdisciplinary approach which goes well beyond the conventional academic endeavor to separate the authentic from the fake. Fakes and Forgers of Classical Literature comprises essays from an international cast of scholars who, in their diverse and creative approaches to questions of authenticity both old and new, radically revise the position of the forged text in the literary tradition and, in light of modern approaches of philology and literary criticism, offer exciting new strategies for understanding forgery and the play with authenticity within ancient literature itself.